UNMANNED AUTONOMOUS VEHICLES: CHALLENGES IN DEVELOPMENT AND MILITARY APPLICATIONS AND THE NEED FOR NEW COMPETENCIES OF MILITARY PERSONNEL - Stankovic, Momir; Bujakovic, Dimitrije (The Policy of National Security, 2025)
The development of unmanned autonomous vehicles represents one of the most dynamic directions of contemporary technological evolution, with increasingly widespread applications in the civilian and primarily the military domain. Although unmanned and autonomous vehicles are often used interchangeably, this paper highlights their essential distinction and the importance of integrated decision-making capabilities for achieving full autonomy. Modern trends in the production of sensors, communication, and power components have enabled the development of complex systems for environmental perception, path planning, and motion control, significantly influencing the transformation of concepts in military operations. The paper analyzes the historical development of unmanned autonomous vehicles, the levels of their autonomy, and their impact on the execution of modern military operations. Considering the pace of technological advancement and achievements, an even more intensive use of autonomous systems can be expected in future armed conflicts, which imposes the need to define the required knowledge and competencies for military personnel involved in their development and operational use. These competencies include mechatronics, automatic control, guidance, artificial intelligence, deployment tactics, logistical support, and others. The paper recognizes the need to enhance military education by integrating technological innovations and developing new academic programs to train personnel capable of creating, maintaining, and efficiently operating unmanned autonomous systems in a dynamic security environment.